Alternative energy imaginaries: Implications for energy research, policy integration and the transformation of energy systems. (March 2021) - Genus, Audley; Iskandarova, Marfuga; Goggins, Gary; Fahy, Frances; Laakso, Senja
Abstract: The paper highlights shortcomings in the contribution of qualitative social sciences and humanities (SSH) research to tackling challenges connected with energy and climate change. These shortcomings are illustrated based on analysis of data gathered in relation to EU (e.g. Horizon 2020; FP7) and European national research funding and energy policy. The paper finds that a techno-economic energy imaginary continues to dominate European energy systems and governs expectations of energy research and its conduct, the integration of SSH with energy policy-making and the framing and foci of policy. A more nuanced, context-sensitive approach is presented as an alternative 'practices and cultural change' energy imaginary. This emphasises attention to social practices relevant to energy use, interdisciplinarity and the coproduction of knowledge with diverse actors. Adoption of such an imaginary can help to enhance policy integration of SSH and the contribution of SSH to ameliorating energy and climate change challenges while providing insight into why gaps occur between (supra)national energy policy and local practices.